Negro Cotaxtla-91, nueva variedad de frijol para las zonas tropicales de Veracruz - Lopez S., E.=700 1 Rodriguez R., R.; Becerra L., E.N.; Cano R., O.
(En, Es)
ilus., 3 ref.
Keywords: PHASEOLUS VULGARIS; VARIEDADES; HIBRIDOS; MEXICO